Successful treatment of radiation-induced mucositis with proton pump inhibitor administration: A report of two laryngeal cancer cases. Issue 1 (February 2017) - Eguchi, Kohtaro; Suzuki, Masami; Ida, Shota; Kudo, Shigehiro; Ando, Ken; Ebara, Takeshi; Higuchi, Keiko
Abstract: Presently, the relationship between laryngopharyngeal reflux (LPR) and radiation-induced mucositis has not been fully explored. In the present study, we report 2 cases of laryngeal cancer in which radiation-induced mucositis ameliorated after proton pump inhibitor (PPI) administration. Case 1 was diagnosed with T1aN0M0 right glottis carcinoma and was treated with radiation therapy. Grade 3 mucositis occurred after administration of 46 Gy irradiation. PPI was administered and mucositis ameliorated quickly without cessation of radiation therapy. Case 2 was diagnosed with T2N0M0 supraglottic cancer and was treated with concurrent chemoradiation therapy. Grade 3 mucositis occurred after administration of 44 Gy irradiation. PPI was administered and mucositis ameliorated quickly without cessation of chemoradiation therapy. In both cases, a remarkable therapeutic effect of PPI was observed in the perilaryngeal areas including the epiglottic vallecula, arytenoid, and postcricoid area. In both cases, LPR involvement was suspected before the onset of radiation therapy. The two cases presented here, indicated a causal relationship between LPR and radiation-induced mucositis. In cases of severe mucositis in the perilaryngeal area in patients with LPR prior to radiation therapy, PPI administration may be an effective therapeutic option.